GE_GERICHTE C/22957/2018 vom 14. Juni 2019 - GE Cour de justice (2019)
SUCCESSION;RÉPUDIATION(DROIT SUCCESSORAL);PROCÉDURE DE FAILLITE;ACTION EN CONTESTATION;COMPÉTENCE | CC.566; CC.573; LP.199.al1.ch1